Mysticism and the Reformation: a brief survey - B. McGinn (Acta Theologica)
A number of influential theologians over the past two centuries have denied that Protestant Christianity has a place for mysticism understood as the mingling of the divine and human natures. Today a more adequate understanding of the mystical element of Christianity as a deeper awareness of God’s presence in the life of believers suggests a new evaluation of the relation of Protestantism and  mysticism, beginning Martin Luther, and continuing with figures like Johann Arndt, and a number of the “Spiritual Reformers,” such as Andreas Karlstadt, Sebastian Franck, Valentin Weigel, as well as the theosophical Lutheran Jacob Boehme. This essay is designed to reopen the question of the relation between Protestantism and mysticism.